Prevalence and intensity of parasites in domestic ducks - Musa, Sharmin; Rahman, Tania; Khanum, Hamida (Dhaka University Journal of Biological Sciences, 2012)
DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11518 Dhaka Univ. J. Biol. Sci. 21(2): 197-199, 2012 (July)